(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Background: In India suicide is a national social issue. India accounts for a large proportion of all suicide deaths globally. Patterns and rates of suicide differ in various populations and cultures. Thus, we aimed to report time trends of suicide deaths, and the association between various attributes such as gender, age of suicide victims, pattern of suicide, etc. Material and Method: This retrospective study, data were obtained from cases of suicide reported to the Department of Forensic Medicine & Toxicology, Dr. Baba Saheb Ambedkar Medical College and Hospital, New Delhi, over a period of 5 years from January 2014 to December 2018. Result: A total of 4973 autopsies were conducted of which suicidal cases contributed to 15.76% (784) of cases. Out of 784 suicidal cases, 530 (67.61%) were male and 254 (32.39%) were female. Most of the victims (38.5%) were from the age group 20-30 years. A significant interaction effect between pattern of suicide and age-group was found. Hanging was most common pattern of suicide followed by poisoning in both sex groups. Conclusion: Male preponderance (67.61%) in suicidal cases was found in this study, and the most involved age group was 21-30 years which is similar to findings found in different other countries.